Australian Public Universities: Are They Practising a Corporate Approach to Governance? - Christopher, Joseph (Routledge, 2014)
This article draws on the multi-theoretical approach to governance and a qualitative research method to examine the extent to which the corporate approach is practised in Australian public universities. The findings reveal that in meeting the needs of multiple stakeholders, universities are faced with a number of structural, legalistic, and behavioural issues that are in tension with the corporate culture. The findings emerging from the interview data are: (a) the current constraints on the structural and operational framework of Australian public universities do not support corporate managerialism; and (b) the current governance framework of Australian public universities supports a pseudo-management culture. The findings help to explain the consequent type of governance control processes to be developed and implemented within the sector, and challenge the current myth that these universities are practising a corporate approach. The findings provide avenues for further research to confirm the findings.